Board of Director Diversity in “Bhinneka Tunggal Ika” Concept - Nor Rahma Rizka; Rika Meidiana Rahayu; Yacobus Soegiarto (Jurnal Akuntansi dan Pajak, 2022)
One of the mechanisms to implement good corporate governance is board of directors diversity. Studies found the board of directors diversity has a positive effect on firm performance. Bhinneka Tunggal Ika philosophy is the best symbol of unity in diversity of Indonesian. This study reflects the concept of "Bhineka Tunggal Ika" using an interpretive paradigm on the board of director diversity that can support the improvement of firm performance. This study uses library research. The results of this study found that the concept of “Bhinneka Tunggal Ika” is very suitable if applied to board diversity of board directors, especially in Indonesia.